Penggunaan Aplikasi KINARUL (Kisah Nabi dan Rasul) untuk Meningkatkan Minat Belajar Siswa pada Pembelajaran PAI di SD - Amulistia Amulistia; Eneng Nenden Rahayu; Nur Aulia Rahmah; Ani Nur Aeni (Departement of Mathematics Education, 2023)
Learning media is a tool or means used to facilitate the teaching and learning process with the aim of helping students to understand concepts or subjects more easily and effectively. This research aims to investigate the effect of the android-based learning media “Kinarul Application”on increasing students’interest in learning. This research was conducted using the Design and Development (D&D) approach,with a series of studies on the analysis,design,development,and implementation processes. Data were obtained through documentation and assessment instruments distributed to islamic education teachers in elementary schools and high level students in elementary schools. Data processing was conducted quantitatively. The result showed that the android-based learning application “Kinarul Application” as a digital learning media for islamic education in elementary schools is quite helpful in delivering learning because of its attractive design in terms of colors,images,and animations contained in the kinarul application. Not only the materials contained in the kinarul application,but there are also songs of the prophets and exercises that contain the stories of the prophets, making the learning activities more varied and interesting to increase students’learning motivation.